Test Distribution Systems: Network Parameters and Diagrams of Electrical Structural - Mahdavi, Meisam [UNESP]; Alhelou, Hassan Haes; Cuffe, Paul (Institute of Electrical and Electronics Engineers (IEEE), 2021)
Nowadays, specialized literature uses different test systems to verify their proposed models and methodologies regarding reconfiguration and operation of distribution networks. However, none of these research works include various test systems with enough information in order to endorse studies that approach distribution system reconfiguration and operation issues. This paper contains several test systems including the load data, network configuration, line characteristics, maximum current of branches, and nominal powers and voltages. The main objective is to provide all the details and information required to evaluate models and methods developed for reconfiguration and operation of radial distribution systems. Verification of all presented data and information has been performed by solving the network reconfiguration problem using established techniques. Moreover, in order to check the radiality of test systems and correctness of their given data, a data visualization technique is employed to online depict network topologies based on the electrical distance between buses.
Keywords: Data visualization; electric power distribution networks; reconfiguration and operation; test systems